Neuropsychology of the parietal lobe: Luria’s and contemporary conceptions - Souza-Couto, Dyecika; Bretas, Rafael; Aversi-Ferreira, Tales Alexandre (Frontiers in Neuroscience, 2023)
The parietal lobe, constituting approximately 20% of the human brain, comprises two main regions: the somatosensory cortex and the posterior parietal cortex. The former is responsible for receiving and processing information from the organism itself or its external environment, while the latter performs concurrent summaries and higher cognitive functions. The present study seeks to integrate modern research findings with Luria’s previous discoveries in order to gain a nuanced understanding of the roles assigned to the parietal lobe as well as its lateralization differences.